Aid for Trade and Services Export Diversification in Recipient-Countries - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2020)
This article examines the effect of Aid for Trade (AfT) flows on services export diversification in recipient-countries. The empirical analysis has relied on a sample of 100 recipient-countries (of which 31 Least developed countries – LDCs) over the period 2002-2014 and used the two-step system Generalized Methods of Moments (GMM) approach. It shows that total AfT flows always exert a positive effect on services export diversification over the full sample, with the magnitude of this positive effect being higher for less advanced countries such as LDCs than for relatively advanced economies. This finding also applies to the effect of the cumulated AfT flows on services export diversification. However, we find that the components of total AfT flows - namely AfT for services sectors and AfT for non-services sectors - exert a higher positive effect on services diversification in less advanced countries, notably LDCs than in relatively advanced countries. Specifically, for countries whose real per capita income exceed a certain level, these two types of capital inflows are associated with greater services export concentration. These findings have important policy implications for developing countries and notably the poorest countries among them.
Keywords: F1; F14; F35; 330; Aid for Trade; Services Export Diversification